Synthesis and characterization of metal oxide nanoparticle from zebra fish (Danio rerio) extract - POONGOTHAI. A,; RAGUL. V, (International Journal of Pharma and Bio Sciences, 2017)
Nanotechnology is now creating a growing sense of excitement in the life sciences especially biomedical devices and Biotechnology. Nanoparticles exhibit completely new or improved properties based on specific characteristics such as size, distribution and morphology. Nanotechnology is a theoretical and experimental field of applied science and technology. It is an engineering of functional systems at the molecular level, covers broad ranges of topics and it focused on controlling and exploring the structure of matter on a range scale below 100 nanometers. Nanotechnology is often referred to as general purpose technology because it has significant impact on almost all industries and all areas of society. Nanoscience and nanotechnology are recent revolutionary development in science and engineering that are evolving at a very fast place. It is driven by the desire to fabricate materials with novel and improved properties thus in likely to impact virtually all are of the physical and chemical science biological and health science. Nano-biotechnology is the most evolving field of nanoscience which covers nanoparticles for numerous biomedical applications and therapeutic treatment for cancers. It is one of the most dynamic areas in modern science. The present study carried out to synthesis and characterization of metal oxide nanoparticles synthesized form whole homogenized zebra fish extract. It clearly indicated that the four and two mixtures metal oxide nanoparticle mixed with zebra fish extract by Ultra violet- Spectroscopy could revealed the presence of nanoparticles types in the zebra fish extract. Therefore metal oxide nanoparticles of zebra extract recommended as biocompatibility, toxicity and in vitro and in vivo targeting efficiency.